Nanostructured Lipid Carriers Based Gel of Methotrexate for Rheumatoid Arthritis: Development, Characterization and Optimization through Taguchi Design - Arya, Malti; Porwal, Amit; Kymonil, Koshy Mamman (Indian Journal of Pharmaceutical Education and Research, 2025)
Background: The goal of this work was to develop, optimise and characterise nanostructured lipid carriers containing methotrexate for the treatment of Rheumatoid Arthritis (RA). As materials and process parameters, solid lipid, surfactant and stirring time were originally tested. The best alternative was chosen, and additional optimisation was performed using Taguchi orthogonal (L9) array design. Materials and Methods: Several batches of NLCs have been generated using the microemulsion process using liquid lipid (castor oil, almond oil and canola oil), solid lipid (cetyl alcohol) and surfactant. The dependent variables for optimisation were particle size, zeta potential, Entrapment Efficiency (EE) and in vitro release. The gel formulation was developed by combining NLCs with carbopol 940 (1% w/v) and was tested for stability, skin permeability (via goat-knee skin), skin irritation and antiarthritic properties. Results: The optimised NLCs (NLC9) had average particle sizes, zeta potentials and EE values of 136.2±5.4, -25.0 mV and 89.47±6.8%. Skin penetration studies revealed that NLCs may successfully penetrate the skin. The gel did not irritate the rabbits' skin, according to the Draize test (PDI=0.00). A conventional formulation was compared to a gel containing NLCs. The in vitro research found that NLCs gel (about 27%) and conventional tablets (about 18%) might reduce arthritic inflammation caused by intra-articular carrageenan injection. Conclusion: The study's findings supported NLCs gel-based formulation's promise as a stable, skin-permeable, non-irritant and patient-compliant rheumatoid arthritis administration approach.
Keywords: Methotrexate; Nanostructured Lipid Carriers; Rheumatoid Arthritis; Taguchi design; Gel; Intra-articular carrageenan injection